2023
DOI: 10.1088/1361-6528/acc038
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrocatalytic performance for oxygen evolution reaction via active interfaces of Co3O4 arrays@FeO x /Carbon cloth heterostructure by plasma-enhanced atomic layer deposition

Abstract: Oxygen evolution reaction (OER) is a necessary procedure in various devices including water splitting and rechargeable metal-air batteries but required a higher potential to improve oxygen evolution efficiency due to its slow reaction kinetics. In order to solve this problem, a heterostructured electrocatalyst (Co3O4@FeOx/CC) is synthesized by deposition of iron oxides (FeOx) on carbon cloth (CC) via plasma-enhanced atomic layer deposition (PE-ALD), then growth of the cobalt oxide (Co3O4) nanosheet arrays. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Hydrogen, a renewable and storable energy carrier with net-zero emissions, is regarded as a potential candidate for conventional fossil fuel [1][2][3][4]. Exactly, the electrochemical water splitting could offer a promising and sustainable route to generate hydrogen on a large scale executed through two half-reactions of hydrogen and oxygen evolution reaction (HER/OER) [5][6][7][8][9]. However, the Earth's freshwater resources are scarce and rapidly decreasing, seriously confining their industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen, a renewable and storable energy carrier with net-zero emissions, is regarded as a potential candidate for conventional fossil fuel [1][2][3][4]. Exactly, the electrochemical water splitting could offer a promising and sustainable route to generate hydrogen on a large scale executed through two half-reactions of hydrogen and oxygen evolution reaction (HER/OER) [5][6][7][8][9]. However, the Earth's freshwater resources are scarce and rapidly decreasing, seriously confining their industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…All these made the ZnO-coated PP nonwoven fabrics particularly suitable for serving as the outer layer of face-masks. Using ALD (PE-ALD), Zhu et al [11] deposited FeO x on carbon cloth (CC) for growing Co 3 O 4 nanosheets. It was found that the ALD cycle number of FeO x strongly affected the growth, distribution, and electronic conductivity of the Co 3 O 4 nanosheets.…”
mentioning
confidence: 99%